2001
DOI: 10.13031/2013.7025
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Characterization of Raw Oil Products From the Thermochemical Conversion of Swine Manure

Abstract: ABSTRACT. In this study, the raw oil products from a thermochemical conversion process of swine manure were characterized based on elemental composition, benzene solubles, heating value, and water content. The analytical results of 78 samples showed that the raw TCC oil products had an average elemental composition of 71.1% carbon, 8.97% hydrogen, 4.12% nitrogen, 0.2% sulfur, and 3.44% ash t is very important that biomass-derived oils are characterized in order to utilize them directly as fuel or for further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…HTL of biowaste aims at not only producing biocrude oil but also mitigating the negative environmental effects of conventional biowaste disposal, such as greenhouse gas emissions and leachate during degradation in landfills . In 2000, He et al reported conversion of swine manure into biocrude oil with a lab-scale batch reactor. Based on the batch test, Ocfemia et al , developed and evaluated a continuous stirred tank reactor with a processing capacity of 2 L/h to convert swine manure into biocrude oil.…”
Section: Introductionmentioning
confidence: 99%
“…HTL of biowaste aims at not only producing biocrude oil but also mitigating the negative environmental effects of conventional biowaste disposal, such as greenhouse gas emissions and leachate during degradation in landfills . In 2000, He et al reported conversion of swine manure into biocrude oil with a lab-scale batch reactor. Based on the batch test, Ocfemia et al , developed and evaluated a continuous stirred tank reactor with a processing capacity of 2 L/h to convert swine manure into biocrude oil.…”
Section: Introductionmentioning
confidence: 99%